LIABILITY OF MINING BUSINESS LICENSE HOLDERS FOR THE IMPLEMENTION OF PRODUCTION OPERATIONS - Sindy, Salsabila Kharisma (Pusat Unggulan Ipteks-PUI Universitas Jambi, 2025)
Coal mining is a long-term activity. The most basic characteristic of coal mining activities is clearing land and resulting in changes in shape after use. This research will discuss the liability of mining license holders and in the context of civil law, as well as post-mining reclamation guarantee funds in mining activities. The method used in this research is the normative method, which conducts research by referring to legal regulations and current legal products. Coal mining is regulated in Law Number 3 of 2020 Amendment to Law Number 4 of 2009 concerning Mineral and Coal Mining. The implementation of the Minerba Law is followed by a form of responsibility regulated in Government Regulation Number 78 of 2010 concerning Reclamation and Post-mining, and regarding liability in civil law is regulated in Article 1365 of the Civil Code. Meanwhile, the form of post-mining reclamation guarantee funds is regulated in Article 100 of the Minerba Law. Mining business license holders in carrying out their activities cannot be separated from the existence of responsibility in carrying out production operation activities, although there are provisions that strengthen legal protection, there are still criticisms and things that weaken.